СУФИЗМ-ИСЛАМДАҒЫ ГУМАНИСТЛИК ТӘЛИЙМАТ - Атамуратова, М.Ж. (FAN va JAMIYAT, 2020)
This article discusses the teachings of Sufism as an Islamic philosophical doctrine that has risen to the level of universal values, and discusses the importance of its humanistic ideas for human excellence.